Short Term Clinical and Angiographic Outcome of Skeletonized Harvesting Technique of Left Internal Mammary Artery, Compared to Pedicled Harvesting for Coronary Revascularization - Sazzad, Md Faizus; Moniruzzaman, Mohammad; Chanda, Prasanta Kumar; Ahmed, Mir Nesar Uddin; Rasheed, Haroon; Gomez, Noyel Cyprian; Ali, Md Shaukat; Choudhury, Sohel Reza; Malik, Fazila Tun Nesa; Ahmed, Farooque (University Heart Journal, 2018)
We examined the hypothesis that the short term clinical and angiographic outcome of skeletonized Left Internal Mammary Artery (LIMA) is better than that of pedicled LIMA used for revascularization of left anterior descending artery at CABG surgery at the Department of Cardiac Surgery, National Heart Foundation Hospital and Research Institute from May 2011 to April 2012. Accordingly we studied 60 consecutive patients who underwent coronary artery bypass grafting, in which the LIMA was anastomosed to the left anterior descending artery (LAD). In 30 consecutive LIMAs were harvested as a pedicle (Control Group) and another 30 consecutive LIMAs were harvested as skeletonized graft (Experimental Group). Three diameters of the LIMA graft were measured quantitatively in postoperative angiograms performed 6 ± 1 month after the coronary artery bypass grafting; D1, at the origin from the subclavian artery; D2, at the level of the second intercostal space; and D3, just proximal to the anastomosis. Our study shows that, complete skeletonization results in increased graft length 19.71 ± 1.77 cm in skeletonized group vs. 17.08 ± 0.71cm in pedicle group (p <0.001). Although there was similar incidence of superûcial wound complications between the groups, the post CABG pain (PCP) was significantly higher in pedicled group at the 6 month follow-up. Check coronary angiography showed the LIMA grafts to the LAD were all patent. There was increased diameter achievement in skeletonized group at the anastomotic site (D3: 1.78 ± 0.21 mm vs. 1.66 ± 0.18 mm; p = 0.03). We conclude that skeletonized LIMA showed a better functional behavior, giving longer conduit length and superior postoperative clinical and angiographic profile. University Heart Journal Vol. 12, No. 2, July 2016; 82-87